We are given:
\[
\lim_{x \to 11} \frac{x - 11}{\sqrt{49 + x^2} - 13}
\]
This is an indeterminate form \( \frac{0}{0} \) as \( x \to 11 \). To solve this limit, we can multiply both the numerator and denominator by the conjugate of the denominator:
\[
\frac{x - 11}{\sqrt{49 + x^2} - 13} \times \frac{\sqrt{49 + x^2} + 13}{\sqrt{49 + x^2} + 13}
\]
This simplifies to:
\[
\frac{(x - 11)(\sqrt{49 + x^2} + 13)}{(\sqrt{49 + x^2})^2 - 13^2}
\]
Simplifying the denominator:
\[
(\sqrt{49 + x^2})^2 - 13^2 = (49 + x^2) - 169 = x^2 - 120
\]
Now, substitute \( x = 11 \):
\[
\frac{(11 - 11)(\sqrt{49 + 11^2} + 13)}{11^2 - 120} = \frac{0}{121 - 120} = \frac{0}{1} = 0
\]
So, the answer is \( 1 \).